Influence of cooling lubricants on the surface roughness and energy efficiency of the cutting machine tools - Jersák, Jan; Simon, Sylvio (Zielona Góra: Uniwersytet Zielonogórski)
The Technical University of Liberec and Brandenburg University of Technology Cottbus-Senftenberg investigated the influence of cooling lubricants on the surface roughness and energy efficiency of cutting machine tools. After summarizing the achieved experimental results, the authors conclude that cooling lubricants extensively influence the cutting temperature, cutting forces and energy consumption.
Keywords: machining; turning; milling; process fluids; minimum quantity lubrication